STUDI KASUS POLA ASUH ORANG TUA TENTANG SEKS EDUKASI PADA ANAK KORBAN KEKERASAN SEKSUAL DI KOTA SAMARINDA - Nella Oktavianna (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
The incidence of sexual violence increased by 44% from 2013 to 2015. Parents have a major role as a giver informasn sex education in preventing the incidence of sexual abuse in children.This study aims to provide an overview upbringing given by parents to children. The research is a qualitative research with case study approach. Key informants are parents of the victims and key informants is the Head KPAID Samarinda. This data retrieval techniques with in-depth interviews. Mechanical analysis using narrative approach. The results showed a lack of dimensional control with aspects of child behavior restrictions, lack of decisive aspect of preventing the sexual behavior of children and lack of control aspects. Dimensions warmth with aspects of the lack of parental supervision, lack of responsiveness and insensitive to children's emotions. It is suggested that parents provide early sex education to children properly and gradual age-appropriate child development. Various sectors also need to be encouraged to prevent and provide proper education to parents about their parenting to children.